The role of electronic management in achieving a competitive advantage for small and medium enterprises. Field study on the Jeddah governorate - Fath El-Din, Ebtisam AbdulQader (Journal of Economic, Administrative and Legal Sciences, 2019)
The aim of the study is to clarify the role of electronic management in creating a high-performance organization, identify the factors necessary for electronic management, identify the obstacles that can face SMEs in transition to electronic management, and identify the general framework of a small or medium company. The researcher used the descriptive analytical method and the questionnaire as a study tool. The study sample consisted of 250 managers of IT units in small and medium enterprises in Jeddah, Saudi Arabia. The study reached a set of findings, namely, there is a positive correlation between the effectiveness of performance in small and medium enterprises and the use of concepts and tools of electronic management. There is a positive statistical relationship between the effectiveness of performance in the organization and the achievement of competitive advantage in small and medium enterprises. There is a positive statistical relationship between the estimated costs of electronic management in the work of small and medium enterprises and the desire to move towards the use of electronic management by owners of small and medium enterprises. The low level of information technology available to SMEs. The study recommended the need to adopt the electronic management of small and medium enterprises, and the need to support government agencies to this trend.
Keywords: role; electronic management; competitive advantage; small enterprises; medium enterprises; Jeddah Governorate